Empirical Bond Sensitivity Testing - Havlíková, Marie; Stádník, Bohumil; Pýcha, Mikuláš; Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví (2021)
The ultimate goal of this thesis is to research the empirical bonds’ price sensitivity to changes in one-year US Treasury rate. The incentive to research this field arises from the fact, that Macaulay duration and other conventional measures of bonds’ interest rate risk often assume the parallel shifts of the yield curves, which however rarely occurs and are typically accompanied by changes of slope and curvature of the yield curve. To achieve the aim, a portfolio of plain-vanilla fixed-coupon bonds with rating varying from AAA to B and coupon rate between one and five percent was assumed, covering the period from 2015 to 2019. The relationship between the one-year US Treasury rate and the bonds’ price was examined based on newly derived duration measure, which was then compared with Macaulay duration of the bonds. The results suggest that, Macaulay duration overestimate the interest rate risk of US Treasury bonds across the whole maturity spectrum. Corporate investment-grade bonds show higher sensitivity for shorter tenors (up to six years). For longer tenors the sensitivity appears to be slightly lower compared to Macaulay duration of the bonds. The high-yield bond, on the other hand, show very low or even no sensitivity to changes in one-year US Treasury rate.
Vedoucí práce: Bohumil Stádník
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví, 2021
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2021
Způsob přístupu: Internet
Keywords: finanční inženýrství [obor dipl. práce]; diplomové práce; master's theses